2009
DOI: 10.1073/pnas.0905833106
|View full text |Cite|
|
Sign up to set email alerts
|

MEK1 mutations confer resistance to MEK and B-RAF inhibition

Abstract: Genetic alterations that activate the mitogen-activated protein kinase (MAP kinase) pathway occur commonly in cancer. For example, the majority of melanomas harbor mutations in the BRAF oncogene, which are predicted to confer enhanced sensitivity to pharmacologic MAP kinase inhibition (e.g., RAF or MEK inhibitors). We investigated the clinical relevance of MEK dependency in melanoma by massively parallel sequencing of resistant clones generated from a MEK1 random mutagenesis screen in vitro, as well as tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
509
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 576 publications
(542 citation statements)
references
References 30 publications
(31 reference statements)
21
509
1
4
Order By: Relevance
“…MEK1/2 mutations, including MEK1 Q56P , have been implicated in both single-agent BRAF and combination BRAF/MEK targeting therapy-acquired resistance in patients (18,21,(34)(35)(36). Single-agent assays demonstrated that relative to the parental BRAF V600E ::MEK1 wt cells, the double-mutant BRAF V600E ::MEK1 Q56P cells displayed a markedly reduced sensitivity to the BRAF inhibitors vemurafenib and dabrafenib and the MEK inhibitor trametinib (Fig.…”
Section: Bvd-523 Exhibits Activity In In Vitro Models Of Braf and Mekmentioning
confidence: 99%
“…MEK1/2 mutations, including MEK1 Q56P , have been implicated in both single-agent BRAF and combination BRAF/MEK targeting therapy-acquired resistance in patients (18,21,(34)(35)(36). Single-agent assays demonstrated that relative to the parental BRAF V600E ::MEK1 wt cells, the double-mutant BRAF V600E ::MEK1 Q56P cells displayed a markedly reduced sensitivity to the BRAF inhibitors vemurafenib and dabrafenib and the MEK inhibitor trametinib (Fig.…”
Section: Bvd-523 Exhibits Activity In In Vitro Models Of Braf and Mekmentioning
confidence: 99%
“…5,24), with recent clinical studies reporting that highly specific BRAF inhibitors are effective in the treatment of metastatic melanoma (25)(26)(27). However, initial promise has been hampered by the development of resistance (28)(29)(30), which is characterized by the reactivation of ERK1/2 (31)(32)(33) and has been attributed to various mechanisms including activating NRAS mutations (29), CRAF overexpression (34), compensatory upregulation of MAP2K kinase COT (28), activating MEK1 mutations (35), and amplification of mutant BRAF (36).…”
Section: Introductionmentioning
confidence: 99%
“…A long period with local control of disease and absence of distant metastasis implies that patients will not have to undergo toxic treatments for metastatic disease, which may accelerate the emergence of mutations and resistant cancer cells (40)(41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%